Response of the Indian summer monsoon to global warming, solar geoengineering and its termination - Mansi Bhowmick (Nature Portfolio, 2021)
Abstract The response of the Indian Summer Monsoon (ISM) to global warming, solar geoengineering and its termination is examined using the multi-model mean of seven global climate model simulations from G2 experiment of the Geoengineering Model Intercomparison Project. Under the global warming scenario, land–ocean temperature contrasts and low-level monsoon circulation progressively strengthen accompanied by enhanced precipitation over the Indian subcontinent. Notably, in the solar geoengineered scenario, marginal surface cooling is projected over the majority of the ISM region, and there is strengthening of both upper and lower level circulation. However, preferential precipitation near Western Ghats leads to dry bias over majority of Indian land. Upon the termination of the geoengineering, the climatic conditions—temperature, precipitation, winds and moisture would abruptly change to what it would have been under the global warming scenario. Thus, this may be important to note that such changes may need attention for the future mitigation and adaptation purposes if solar geoengineering is required to implement in future.